Systematics of peninsular Malaysian scaly tree ferns (Cyatheaceae): phylogenetics, computer-aided identification and conservation - Azi Azeyanty Jamaludin (Tanjong Malim, 2017)
Systematics of peninsular Malaysian scaly tree ferns (Cyatheaceae): phylogenetics, computer-aided identification and conservation by Azi Azeyanty Jamaludin